Leadership Model Visionary Principal in Improving the Professional Attitude of Teachers at MTs Riyadlul Jannah NW Jelojok Kopang Central Lombok - Sujaan; Fathul Maujud (al-Afkar, Journal For Islamic Studies, 2024)
To improve teachers' professional attitudes at MTs Riyadlul Jannah NW Jelojok, Kopang, Central Lombok, this research investigates the principal's visionary leadership model. It is considered important to improve the quality of education, especially in terms of developing teachers' professionalism. The research was conducted through a qualitative approach with a case study as the design. Observation of education and training activities, in-depth interviews with teachers and principals, and analysis of related documents were all methods used to collect data. The results show that principals can use the visionary leadership model to create a positive working environment where teachers are motivated to do new things and work together. In addition, a clear evaluation system and organized training improve teachers' professional attitudes, which are evident in increased discipline and creativity in teaching. The findings suggest that principals are crucial in building a strong culture of professionalism in schools.